Influence of Key Parameter on Contact and Lubrication Performance of the Roller Enveloping Internal Engagement Worm Gear Transmission - Yuanhong Song; Xingqiao Deng; Yuanyuan Jiang; Jinge Wang (Jixie chuandong)
In order to analyze the influence of key parameters on the contact and lubrication performance of the inner meshing worm gear of the roller envelop， the mathematical model of the new worm drive is built. And the lubrication angle and the induced normal curvature equation are constructed by the meshing equation. Then the influence of the key parameters on the lubrication and contact performance of worm drive are analyzed by the numerical calculation method. These key parameters include the center distance，the transmission ratio，roller radius and the worm-wheel rotational deflection. The analysis shows that in these key parameters，the deflection angle of the worm wheel has a great influence on the contact and lubrication performance of the inner meshing worm gearing of the roller envelope. It is suggested that the deviation angle of the worm wheel is the best in the range of 0°to 40°. And the corresponding parameters are selected for 3D modeling analysis to verify the validity of the analysis parameters. The study provides a reference for further research on the roller enveloping internal worm drive.